Financial management of commercial banks - Mason, John M. (Boston : Warren, Gorham & Lamont, 1979)
This volume brings the theory and techniques of corporate finance and microeconomics to bear on matters of importance to commercial bankers. It view is internal to the bank; the perspective taken is that of top management. This book is an outgrowth of a course on the financial management of commercial banks developed at the Wharton School.
Includes bibliographical references and index.
hza 01/08/2018
Loans
Keywords: Bank management; Corporations; Financial management - commercial banks